Dark fermentative hydrogen production by anaerobic sludge growing on glucose and ammonium resulting from nitrate electroreduction. (6th April 2016) - Abdallah, Rawa; Djelal, Hayet; Amrane, Abdeltif; Sayed, Walaa; Fourcade, Florence; Labasque, Thierry; Geneste, Florence; Taha, Samir; Floner, Didier
Abstract: The main objective of this work was to study the feasibility of biohydrogen production by heat-treated anaerobic sludge with glucose as carbon substrate and ammonium as nitrogen source, obtained from the electrochemical reduction of concentrated nitrate solutions (3 g L −1 NO 3 − ), namely model solutions simulating those obtained after physicochemical denitrification of industrial wastewaters. Experiments were realized in bacth systems involving 125 mL (without pH control) and 3 L (with pH control) reactor, respectively. In order to find the optimal conditions for H2 production, the first set of experiments were conducted without pH control at various initial pH (pH 5.5, 6.5 and 7.5) and glucose concentrations (5–30 g L −1 ); and the highest H2 yield (1.1 mol H2 mol − 1 glucose consumed ) was reached for a glucose concentration of 25 g L −1 and at pH 6.5. These optimal conditions were then considered to examine the effect of pH control on biohydrogen production, in a 3 L bioreactor. The pH control allowed a considerable improvement of the hydrogen gas conversion efficiency, which reached 2.02 mol H2 mol − 1 glucose consumed . Highlights: The production of biohydrogen via anaerobic sludge growing on ammonium generated electrochemically was proved. pH control allowed a considerable improvement of the hydrogen gas conversion efficiency. In case of pH control, hydrogen yield was 2.02 mol H2 mol − 1 glucose consumed . Complete assimilation of the obtained NH 4 + (0.86 g L −1 NH 4 + ) was achieved. Environmentally friendly coupled process for hydrogen production and nitrate treatment was developed.